2012
DOI: 10.1016/j.enbuild.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in energy consumption introduced by building operations and weather for a medium-size office building

Abstract: Deviations between predicted and actual building energy consumption can be attributed to uncertainties introduced by four components of such projections: (1) the accuracy of the underlying models in simulation tools, (2) the accuracy of input parameters describing the design conditions of building envelope and HVAC systems, (3) actual weather, (4) variations in building operation practices. This study investigates uncertainties in energy consumption due to actual weather and building operational practices, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(77 citation statements)
references
References 15 publications
(15 reference statements)
1
67
0
Order By: Relevance
“…Kleber and Wagner (2007) monitored an office building and found that failures in operating the building's facilities caused higher energy consumption, and they underline the importance of continuous monitoring of a building. Wang et al (2012a) showed that poor practice in building operations across multiple parameters results in an increase in energy use of 49-79%, while good practice reduces energy consumption by 15-29%. Piette et al (1994) suggest that building operators do not necessarily possess the appropriate data, information, and tools needed to provide optimal results.…”
Section: Poor Practice and Malfunctioning Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Kleber and Wagner (2007) monitored an office building and found that failures in operating the building's facilities caused higher energy consumption, and they underline the importance of continuous monitoring of a building. Wang et al (2012a) showed that poor practice in building operations across multiple parameters results in an increase in energy use of 49-79%, while good practice reduces energy consumption by 15-29%. Piette et al (1994) suggest that building operators do not necessarily possess the appropriate data, information, and tools needed to provide optimal results.…”
Section: Poor Practice and Malfunctioning Equipmentmentioning
confidence: 99%
“…According to Bhandari et al (2012), the predicted annual building energy consumption can vary up to 7% as a function of the provided location's weather data. While Wang et al (2012a) showed that the impact of year-to-year weather fluctuation on the energy use of a building ranges from −4 to 6%. Knowing the uncertainty of related microclimate variables is necessary to understand its impact on energy prediction (Sun et al, 2014).…”
Section: Scenario Uncertaintymentioning
confidence: 99%
“…Eventually, typical years are also necessary for assessing the building energy performance under standard weather reference conditions, which are expected to be representative of the multi-year series in a given location. Some previous studies observed that the variability of buildings annual energy uses are less than 10 % in the multi-year period -between 4 % and 6 % for U.S. climates [8,9] or 4.6 % for Hong-Kong [10]. Although the previous studies are valid only for the climatic context and buildings analysed, they indicate that a single reference year can generally be used to express the typical energy performance.…”
Section: Introductionmentioning
confidence: 90%
“…Prior to proceedings, it is important to highlight that the literature lacks a standard on the design of parametric variation experiments, in particular, the choice of the ranges over which to vary each parameter. Consequently, the authors adopted a conservative approach by using ranges that are smaller than or equal to those used in previous comparable studies [25,26,42]. This ensures that the variations simulated in this study are in line with previously published work on the topic, which helps confirm the validity of the experimental design.…”
Section: Parametric Variationmentioning
confidence: 48%